IDENTIFIKASI JENIS DAN FAKTOR TEMPAT TUMBUH MANGROVE DI DESA KOBI SADAR KECAMATAN SERAM UTARA TIMUR KOBI - Sulistiawati Tobaru; Fanny Soselisa; Irwanto Irwanto (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research was conducted in Kobi Sadar Village, North Seram Timur Kobi District in May 2024. With the aim of 1). To find out the types of mangroves in the mangrove forest in Kobi Sadar Village, North Seram Timur Kobi District 2). To find out the factors where mangroves grow in Kobi Sadar Village, North Seram Timur Kobi District. Data analysis and the approach used for measurements and observations in this study were descriptive qualitative methods and direct on-site surveys. Information collection regarding vegetation is carried out through vertical channels. The process of identifying specimens to find out the species name is carried out by comparing the morphological characteristics of the various types of mangroves found and referring to the guidebook for mangrove identification in Indonesia (MIC and JICA). Vegetation analysis is a step to explore the structure and composition of plants based on the shape and character of the plant collection. The various elements that make up vegetation structure include growth type, level, and canopy closure.